FINANCIAL PERFORMANCE ON COMPANY VALUE WITH FINANCIAL DISTRESS AS VARIABLE INTERVENING IN RETAIL TRADING COMPANIES LISTED ON IDX - Ina Fitriani; Muhammad Toaha; Muhammad Sobarsyah (Hasanuddin Journal of Applied Business and Entrepreneurship, 2021)
This study aims to analyze the effect of financial ratio analysis on firm value with financial distress as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2020. This type of research is causal comparative. Sampling using proportional random sampling method, obtained a sample of 17 companies from 25 company populations with a total of 68 units of observation of analysis. Secondary data collection uses the technique of documenting the annual financial statements of IDX manufacturing companies published on the website www.idx.co.id. Methods of data analysis through classical assumption test, multiple linear regression test and mediation test with path analysis using Sobel test. The results showed that liquidity, solvency, profitability and financial distresss simultaneously and partially have an effect directly significant to the value of retail trading companies listed on the IDX liquidity, solvency and profitability variables have a significant effect on firm value retail trade listed on the IDX through financial distress as an intervening variable.